Evaluating and Auditing a Community College Learning Skills Center Program Second Year - Cohen-Benjamin, Barbara; Olson, Gerald T.; Los Angeles City Coll., CA.; Los Angeles County Superintendent of Schools, CA. ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 1977)
An evaluation of Los Angeles City College's Learning Skills Center (LSC) was conducted in order to ascertain the nature of the LSC's outcomes. The LSC offers students an opportunity to participate in diagnostic and prescriptive open-entry open-exit programs in an individualized setting. Types of programs available through the LSC include communication skills, quantitative skills, and tutoring in other college-level courses. The evaluation of the LSC considered three specific areas: the first consisted of analyses of data gathered in relation to specific program objectives, the second examined unexpected spinoffs, and the third considered the humanistic characteristics of the LSC. Results of the evaluation indicated: (1) students who utilized the LSC's services in the areas of basic math, basic English, accounting, business, and chemistry were associated with significantly lower dropout rates than were students who enrolled in these courses but did not utilize the LSC; (2) the LSC had gained the support of the Academic Senate and a number of departments traditionally opposed to remedial courses; and (3) numerous students who had used the LSC offered favorable personal evaluations of the Center. A critique of the causal-comparative method employed in the study is included. (JDS)
ERIC Note: For a related document see ED 121 408.
Educational level discussed: Two Year Colleges.
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: Basic Skills; Community Colleges; Institutional Research; Learning Laboratories; Persistence; Program Evaluation; Remedial Instruction; Research Methodology; Resource Centers; Skill Centers; Skill Development; Tutoring; Two Year Colleges; Causal Comparative Method -- Los Angeles City College CA; Reports, Research